Perlindungan Hukum Penyelenggara Lelang Non Eksekusi Sukarela Secara Online Terhadap Wanprestasi Yang Dilakukan Oleh Pemenang Lelang - Muchlas, Muhammad Labib; Suharto, Miko Aditiya (Universitas Semarang, 2025)
The problem in this research is the act of default carried out by the auction winner. Article 1 paragraph 29 of Minister of Finance Regulation Number 213/PMK.06/2020 concerning Auction Implementation Instructions explains that buyers are required to pay for the auction object won in the auction no later than 5 (five) working days after the auction. The aim of this research is to understand the problems that occur in the implementation of voluntary non-execution auctions at the Office of the Notary/PPAT/Class II Auction Officer Dr. HR. Ibnu Arly, S.H., M.Kn and IBID Surabaya auction center. As well as to understand the legal protection for auction organizers against auction winners who default. The type of research is juridical-empirical with descriptive qualitative research characteristics. Using a conceptual approach, statutory approach and case approach. Legal materials come from primary legal materials, secondary legal materials and non-legal materials. Procedures for collecting legal materials include observation, interviews and literature study. The research results found that there are two legal protections for auction organizers against defaults committed by auction winners, namely preventive and repressive. As a preventive measure, hold an open house and sellers are required to submit a Land Registration Certificate (SKTP). For repayment, the security deposit belonging to the auction participant who defaults will not be returned and will not be allowed to participate in the auction again for 6 (six) months. Keywords: Legal Protection, Default, Auction.